Violence and Political Myth: Radicalizing Believers in the Pages of Inspire Magazine. Issue 4 (7th December 2015) - Kirke, Xander
Abstract: Violent Jihadist movements have increasingly produced online English language magazines in order to encourage young Muslims into terrorism. This article argues that sociological approaches to the study of these magazines should engage with theories of political myth, understood as the collective "work" on dramatic and figurative narratives which provide significance to the political conditions of social groups. The utility of this approach is demonstrated through an analysis of al-Qaeda's online magazine, Inspire . Targeted toward an alienated young Western Muslim readership, Inspire stylistically mimics Western magazines by using satirical representations of politicians and making references to popular culture. The authors seek to convince their readership that they are part of a violent conflict with Western "crusaders" and treacherous false Muslims. Through a rhetorical strategy of "legitimization via proximization, " perceived injustices committed by the purported enemies of Islam throughout the world are seen as direct attacks on the reader and all Muslims. The reader must sacrifice his/her livelihood in order to become a "hero" and defend the Umma against its enemies. The article concludes that the mobilizing potential of the work on myth in these magazines necessitates further research.